Maternal Social Information Processing and the Frequency and Severity of Mother-Perpetrated Physical Abuse. (November 2016) - Azar, Sandra T.; Miller, Elizabeth A.; McGuier, Devin J.; Stevenson, Michael T.; O'Donnell, Ellen; Olsen, Nina; Spence, Noel
The frequency and severity of physical abuse influences children's outcomes, yet little theory-based research has explored what predicts its course. This study examined the potential role of social information processing (SIP) factors in the course of abuse. Mothers with histories of perpetrating physical abuse ( N = 62) completed measures of SIP, and the frequency and severity of mother-perpetrated physical abuse were collected from Child Protection Services records. Poorer problem-solving capacities were significantly related to greater frequency of physical abuse. Hostile attributions toward children were positively associated with abuse severity. Controlling for demographics and co-occurrence of neglect, SIP factors together accounted for a significant proportion of variance in the frequency of physical abuse, but not severity. With the exception of unrealistic expectations, preliminary evidence supported a link between maternal SIP and the course of abuse perpetration. Future research directions and implications for intervention are discussed.